The smoking behavior and affecting factors of physical education and sports teachers in Turkey - Gundogdu, Cemal (Drunpp-Sarajevo, 2012)
Aim: This study aims to examine the attitudes and affecting factors of physical education and sports teachers towards smoking. Methods: Among a total of 20,074 permanent and contract physical education and sports teachers, 2000 (10%) working in various schools located in different cities in Turkey affiliated with Ministry of National Education during the school year of 2010-2011 were selected using random sampling method. After necessary permissions were granted, an online questionnaire prepared by the researchers was used to collect data, by which 1995 teachers were contacted. Results: The responses of the 1995 (1345 male, 650 female) teachers that filled in the questionnaire form were evaluated. The mean age was 31.02 +/- 4.72 (n=1992). 88.3% of the participants smoked only once during their entire lives. 53.4% smoked everyday, while 11.8% smoked occasionally (n=1990). Gender did not create a statistically significant difference between smoking and non-smoking teachers (n=1990, p>0.05). For both gender groups, the majority of smokers started between the age of 16-20. When smoking behavior was analyzed on the basis of age, it was found that the 26-40 age group had the highest smoking rate. When the participants were asked about the primary factors affecting smoking behavior, the response was friends for 38.7% and pretension for 22.1%. A negative relationship was observed between the level of mother's education and smoking (p<0.05). Male teachers had higher cigarette dependence scores than females (p<0.05). Conclusion: This study suggests that physical education and sports teachers, who are supposed to be a role-model for their students, have a high smoking rate. An urgent action plan is needed to reduce the smoking rate and to increase the quit rate among physical education and sports teachers.
Keywords: Cigarette; Physical Education and Sports Teachers; Habit; Attitude